2018
DOI: 10.1093/nar/gky507
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair factor APLF acts as a H2A-H2B histone chaperone through binding its DNA interaction surface

Abstract: Genome replication, transcription and repair require the assembly/disassembly of the nucleosome. Histone chaperones are regulators of this process by preventing formation of non-nucleosomal histone–DNA complexes. Aprataxin and polynucleotide kinase like factor (APLF) is a non-homologous end-joining (NHEJ) DNA repair factor that possesses histone chaperone activity in its acidic domain (APLFAD). Here, we studied the molecular basis of this activity using biochemical and structural methods. We find that APLFAD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 62 publications
5
59
0
Order By: Relevance
“…Aprataxin and PNK (Polynucleotide Kinase) like factor (APLF) is a histone chaperone [37]. Apart from histone chaperone activity, APLF is associated with the non-homologous end joining DNA repair pathway [33,38].…”
Section: Histone Chaperones In Breast Cancer Metastasis Aplfmentioning
confidence: 99%
See 2 more Smart Citations
“…Aprataxin and PNK (Polynucleotide Kinase) like factor (APLF) is a histone chaperone [37]. Apart from histone chaperone activity, APLF is associated with the non-homologous end joining DNA repair pathway [33,38].…”
Section: Histone Chaperones In Breast Cancer Metastasis Aplfmentioning
confidence: 99%
“…Apart from histone chaperone activity, APLF is associated with the non-homologous end joining DNA repair pathway [33,38]. The acidic C-terminal domain (AD) of APLF is responsible for histone chaperone activity [37]. APLF AD domain is found to be structurally homologous to NAP1 protein (Nucleosome Assembly protein 1), characterized as a histone chaperone [39].…”
Section: Histone Chaperones In Breast Cancer Metastasis Aplfmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that both histone systems bind the APLF reader protein with micromolar affinity, both are enthalpically favorable interactions, yet the binding of (H3-H4)2 is entropically unfavorable, which might explain the difference in their Kd values. ITC did not detect additional lower affinity binding modes, resulting in a stoichiometry of n = 1 in both cases [141].…”
Section: Binding Affinitymentioning
confidence: 82%
“…ITC is also applicable for the thermodynamic analysis of large complexes of the epigenome. For example, binding of aprataxin and polynucleotide kinase like factor (APLF) to histone dimers and tetramers H2A-H2B and (H3-H4)2 was investigated in a study [141]. It was found that both histone systems bind the APLF reader protein with micromolar affinity, both are enthalpically favorable interactions, yet the binding of (H3-H4)2 is entropically unfavorable, which might explain the difference in their Kd values.…”
Section: Binding Affinitymentioning
confidence: 99%